Адвербіальний простір поетичного мовлення Лесі Українки - Бойко, В. М.; Давиденко, Л. Б. (Видавництво НДУ ім.М. В. Гоголя, 2017)
Стаття присвячена всебічному аналізові адвербіативів поетичних творів Лесі Українки. Окрім морфологічних особливостей та систе-матизації основних підходів до вивчення класу адвербіативів, з’ясо-вано, що прислівник у контексті художнього твору набуває емоційно-експресивного забарвлення. Визначено, що індивідуально-авторське використання прислівників, прислівникових комплексів, редуплікацій, транспозиції сприяє виникненню адгерентної експре-сивності як самих мовних одиниць, так і контексту в цілому.
The article is devoted to a comprehensive analysis of adverbiatives of Lesya Ukrainka's poetic works. In addition to morphological features – the function of expressing the non-process sign of action or condition, immutability and correlation with significant parts of speech – and systematization of the basic approaches to studying the class of adverbiatives, it is established that the adverb acquires an emotionally expressive coloring in the context of the art work. It is determined that the individual-authorial use of adverbs, adverbial complexes, various repetitions, transpositions promotes the emergence of the adherent expressiveness of both the linguistic units themselves and the context as a whole. Modern approaches to the study of the functioning of language units in the context of the art work make it possible to define new aspects of the study of the poetry heritage of Lesya Ukrainka.
Keywords: адвербіатив; прислівники означальні; обставинні; ампліфікація